Why Is the Good Behavior Game Used for Bad Behavior? Recommendations for Using It for Promoting Good Behavior. (December 2019) - Maag, John W.
Although the good behavior game (GBG) has a long empirical record for effectively decreasing inappropriate student behavior, there are fewer studies that have targeted improving appropriate behavior. This article describes why and how the GBG can be used by teachers across grade levels and situations to increase student appropriate behavior and benefit teachers.